A five year retrospective study on maternal and perinatal outcome in pregnancy after cardiac surgery - Rathore, Swati; Shankar, Ravi; Vijjeswarapu, Annie P.; Abraham, Anuja; Yadav, Bijesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Pregnancy is a hypercoaguable state with physiological haemodynamic changes occurring during pregnancy. There is a progressive increase in intravascular volume in second trimester of pregnancy and increase in cardiac output. Pregnancy makes a significant impact on cardiovascular system. It is important to evaluate and study the effect of pregnancy on women with surgically corrected heart conditions so as to preempt potential complications. Methods: This is a retrospective study of patients with prior history of cardiac surgery and their pregnancy outcomes in a tertiary center of Southern India over a period of five years from January 2011 to December 2016. Results: In this study, descriptive statistical analysis was done in 87 women with pregnancy following cardiac surgery. 58.6% were nulliparous. Around 52% had associated obstetric risk factors. The most common cardiac surgery in this population was Mitral valve replacement (40.2%) and Atrial septal defect closure (37.9%). Women belonged to NYHA class I in 90.8% of cases. 58.6% had vaginal delivery and 36.8% had caesarean section. 6 women had postpartum haemorrhage which was medically managed, and 6 women needed ICU care.74.7% women had term deliveries. 18.4 % of the babies were less than 2.5 kg weight at birth. 13 babies required Neonatal ICU care. Conclusions: Maternal and neonatal outcome mainly depends on the functional cardiac status of women before conception. In this study we emphasize on the importance of multidisciplinary team approach involving cardiologist, obstetrician and neonatologist in the management of women with prior cardiac surgery.